Possible New Strategies for the Treatment of Congenital Hyperinsulinism - Sikimic, Jelena; Hoffmeister, Theresa; Gresch, Anne; Kaiser, Julia; Barthlen, Winfried; Wolke, Carmen; Wieland, Ilse; Lendeckel, Uwe; Krippeit-Drews, Peter; Düfer, Martina; Drews, Gisela (Frontiers in Endocrinology, 2020)
Objective Congenital hyperinsulinism (CHI) is a rare disease characterized by persistent hypoglycemia as a result of inappropriate insulin secretion, which can lead to irreversible neurological defects in infants. Poor efficacy and strong adverse effects of the current medications impede successful treatment. The aim of the study was to investigate new approaches to silence β-cells and thus attenuate insulin secretion. Research Design and Methods In the scope of our research, we tested substances more selective and more potent than the gold standard diazoxide that also interact with neuroendocrine ATP-sensitive K+ (KATP) channels. Additionally, KATP channel-independent targets as Ca2+-activated K+ channels of intermediate conductance (KCa3.1) and L-type Ca2+ channels were investigated. Experiments were performed using human islet cell clusters isolated from tissue of CHI patients (histologically classified as pathological) and islet cell clusters obtained from C57BL/6N (WT) or SUR1 knockout (SUR1-/-) mice. The cytosolic Ca2+ concentration ([Ca2+]c) was used as a parameter for the pathway regulated by electrical activity and was determined by fura-2 fluorescence. The mitochondrial membrane potential (ΔΨ) was determined by rhodamine 123 fluorescence and single channel currents were measured by the patch-clamp technique. Results The selective KATP channel opener NN414 (5 µM) diminished [Ca2+]c in isolated human CHI islet cell clusters and WT mouse islet cell clusters stimulated with 10 mM glucose. In islet cell clusters lacking functional KATP channels (SUR1-/-) the drug was without effect. VU0071063 (30 µM), another KATP channel opener considered to be selective, lowered [Ca2+]c in human CHI islet cell clusters. The compound was also effective in islet cell clusters from SUR1-/- mice, showing that [Ca2+]c is influenced by additional effects besides KATP channels. Contrasting to NN414, the drug depolarized ΔΨ in murine islet cell clusters pointing to severe interference with mitochondrial metabolism. An opener of KCa3.1 channels, DCEBIO (100 µM), significantly decreased [Ca2+]c in SUR1-/- and human CHI islet cell clusters. To target L-type Ca2+ channels we tested two already approved drugs, dextromethorphan (DXM) and simvastatin. DXM (100 µM) efficiently diminished [Ca2+]c in stimulated human CHI islet cell clusters as well as in stimulated SUR1-/- islet cell clusters. Similar effects on [Ca2+]c were observed in experiments with simvastatin (7.2 µM). Conclusions NN414 seems to provide a good alternative to the currently used KATP channel opener diazoxide. Targeting KCa3.1 channels by channel openers or L-type Ca2+ channels by DXM or simvastatin might be valuable approaches for treatment of CHI caused by mutations of KATP channels not sensitive to KATP channel openers.